2023
DOI: 10.3389/fpsyt.2022.1067228
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of the COVID-19 pandemic on the mental wellbeing of health care workers on sustainable employability: A scoping review

Abstract: Sustainable employability (SE) amongst healthcare workers (HCW) is an important asset for healthcare institutions. However, SE is under strain due to high work pressure, a shortage of employees, and absenteeism amongst employees based on mental problems. These developments had already started before the COVID-19 pandemic. The aim of this review is to explore whether there is a moderating effect of the COVID-19 pandemic on the mental wellbeing of HCW in the context of SE. A double blinded systematic review was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Which is a considerable increase compared to the reported pre-pandemic prevalence of 10% among nurses in Sweden [ 10 ], and 12% among nurses in Europe and Central Asia [ 11 ]. This indicates that, like other countries [ 34 ], the COVID-19 pandemic negatively impacted the psychological well-being among healthcare workers in Sweden.…”
Section: Discussionmentioning
confidence: 72%
“…Which is a considerable increase compared to the reported pre-pandemic prevalence of 10% among nurses in Sweden [ 10 ], and 12% among nurses in Europe and Central Asia [ 11 ]. This indicates that, like other countries [ 34 ], the COVID-19 pandemic negatively impacted the psychological well-being among healthcare workers in Sweden.…”
Section: Discussionmentioning
confidence: 72%
“…During the COVID-19 pandemic, healthcare workers have been shown to be affected in different contexts such as individual, interpersonal, institutional, social and political (Chemali et al, 2022). It is stated that in this period mental wellbeing of HCWs was affected and certain experiences can have devastating effects on both the personal and professional lives of healthcare workers (Boamah et al, 2023; Byrne et al, 2023; Chemali et al, 2022; van den Broek et al, 2023). From this point of view, the fact that HCWs increase alcohol and cigarette use for relaxation and socialization is a finding that should be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been shown that the increase in COVID-19 risk perceptions of healthcare workers statistically increased their death anxiety decreased their life satisfaction and psychological well-being (Özer et al, 2023). Moreover, it has been shown that this infection has a particular negative impact on the well-being of healthcare workers (Boamah et al, 2023; Byrne et al, 2023; Chemali et al, 2022; van den Broek et al, 2023; Wańkowicz et al, 2020). During the COVID-19 pandemic, healthcare workers have been shown to experience many negative conditions such as physical fatigue, anxiety, insomnia, and psychological distress (Diomidous, 2020; García-Martín et al, 2020; Labrague, 2021; Sagherian et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings of a recent scoping review ( 15 ) preventing MHCW from mental health problems and maintain sustainable employment during pandemic waves, it is pivotal to use a systematic mental health tool frequently. Screening MHCW with regards to mental health problems provides early protection and realizes the opportunity to signalize future problems and prevent MHCW from sick leave and/or even resigning.…”
Section: Introductionmentioning
confidence: 99%